The role of science in the practice of talent identification: a case study from gymnastics in New Zealand - Kerr, R. (Sport in Society: Cultures, Commerce, Media, Politics, 2019)
Talent identification is an example of a practice where `scientism threatens to engulf us all.` Talent identification and development are areas where models perceived to be scientific have been uncritically adopted into sporting practice due to the belief that they represent best practice. In this article, I track the changing talent identification systems adopted in the sport of rhythmic gymnastics in New Zealand over approximately 20 years. The findings revealed that those in decision-making positions originally adopted the perspective of scientism in introducing a physical ability test which they perceived to have scientific value. However, scientific testing was later removed owing to the now empowered gymnastics coaches drawing on what Foucault referred to as local knowledge, acquired through their own experiences. Their experiences resulted in the coaches believing in the importance of what Latour described as social practices being more significant in talent identification than scientific testing.